(Re)configurações territoriais da produção orgânica do Agreste Central de Sergipe à luz das potencialidades ambientais - Santos, Clêane Oliveira dos (2016)
This research aims to analyze the environmental potentialities present in the effectiveness of area of organic agriculture in Sergipe Central Arid zone. It appears that the spreading of organic agriculture in Sergipe is taking place thanks to the construction of new social and environmental coexistence level values associated with the changes in management practices. The area of this analysis are the municipalities of Areia Branca, Itabaiana and Malhador, which are part of the territory of Central Sergipe Arid zone. To develop this research the study methodology was structured in three stages: Cabinet, which covers literature research, visiting the agencies and entities for secondary data collection and mapping survey; field step comprises study area observation and recognition, location points marking, semi-structured interviews application and the photographic survey; the last step is called synthesis, since the achieved results in the two previous steps will be analyzed wether the initial study hypothesis is proven or not. This geographical area methodological theoretical model of evaluation is related to the definition / evaluation of potentialities environmental indicators. Thus, the construction of these as instruments of potentialities environmental indicators matrix allowed a simplified and qualitative reading of environmental, social, economic and cultural needs of the study area, showing the organic system new territoriality configuration. Therefore, the analysis concluded that the surveyed municipalities have potentialities features that favor the development of organic farming, however, they also have limitations that contribute to slower growth of organic production in the study area. Thus, the potentialities are environmental sphere related, such as the use of natural resources and the practice of environmental conservation, and also the influence of historical tradition in the production and marketing of foodstuffs in the Arid zone. As for the limitations, they are related to difficulties in the social, economic and political spheres that hinder the full development of organic production.